Agile Processes in Software Engineering and Extreme Programming 14th International Conference, XP 2013, Vienna, Austria, June 3-7, 2013, Proceedings - Baumeister, Hubert; Weber, Barbara; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book contains the refereed proceedings of the 14th International Conference on Agile Software Development, XP 2013, held in Vienna, Austria, in June 2013. In the last decade, the interest in agile and lean software development has been continuously growing. Agile and lean have evolved from a way of working -- restricted in the beginning to a few early adopters -- to the mainstream way of developing software. All this time, the XP conference series has actively promoted agility and widely disseminated research results in this area. XP 2013 successfully continued this tradition. The 17 full papers accepted for XP 2013 were selected from 52 submissions and are organized in sections on: teaching and learning; development teams; agile practices; experiences and lessons learned; large-scale projects; and architecture and design.
Barriers to Learning in Agile Software Development Projects -- Early Start in Software Coaching -- Introducing Programmers to Pair Programming: A Controlled Experiment -- Team Performance in Agile Development Teams: Findings from 18 Focus Groups -- The Practice of Not Knowing for Sure: How Agile Teams Manage Uncertainties -- Key Challenges of Improving Agile Teamwork -- Effects of Negative Testing on TDD: An Industrial Experiment -- Investigating the Impact of Experience and Solo/Pair Programming on Coding Efficiency: Results and Experiences from Coding Contests -- Visualizing and Managing Technical Debt in Agile Development: An Experience Report -- How Are Agile Methods and Practices Deployed in Video Game Development? A Survey into Finnish Game Studios -- Inter-organizational Co-development with Scrum: Experiences and Lessons Learned from a Distributed Corporate Development Environment -- A Metrics Model to Measure the Impact of an Agile Transformation in Large Software Development Organizations -- Perspectives on Productivity and Delays in Large-Scale Agile Projects -- Continuous Release Planning in a Large-Scale Scrum Development Organization at Ericsson -- Micro Patterns in Agile Software -- Feature Usage Diagram for Feature Reduction -- The Effect of Complexity and Value on Architecture Planning in Agile Software Development.
Keywords: Software engineering; Management information systems; Computer science; Software Engineering; Management of Computing and Information Systems